A comparison of Qin Pai and Jiangnan Pai Erhu performance practice based on Qinfeng and Jiangnan Chunse / Xi Chen - Xi, Chen (2017)
This study examined into the area of performance practice on erhu examining two schools of playing Northern and Southern China: Qinpai and Jiangnan pai. Pai or school refers to a stylistic feature and performance technique that closely relate to its place of origin. Qinpai erhu developed in the 1950s formed a musical style that fuse between local folk and traditional music genre from Shaanxi. Jiangnan school of erhu playing originated from the Jiangnan and popular in Shanghai, Jiangsu and Zhejiang province reveals anther musical style. Past literatures discussed the various styles of erhu playing, however, lacking in research on performance practice between the Qin and Jiangnan erhu schools of playing. Detailed discussion over the two major repertoire Qinfeng and Jiangnan Chunse is absent in past literatures. This paper discussed Qinpai and Jiangnan pai unique playing style and techniques. The differences between the two are analysed based on two representative repertoire Qinfeng and Jiangnan Chunse. Methodology includes participant observation, score analysis, transcription and a discussion that includes a self-reflexive account on the performance of the two pieces. The research outcome gathered various pedagogical concern in terms of performance practice that provides a reference for future scholars and erhu players.